The Effect Of Electronic Banking On The Performance Of Companies In The Banking Sector Listed On The Indonesia Stock Exchange - suci ramadani (UNIB Press, 2022)
This research aims to examine and analyze the effect of the provision of electronic banking (ATM and Mobile banking) of financial performance againts banking by using banking data listed on the Indonesia stock exchange (BEI) in 2018-2020. This saw the current banking condition requaires banks to adapts with condition and situation that happened because technological development will have an impact in all aspects of life, including the world of banking. This type of research is quatitative, sampling uses a purposive sampling technique. With the number of samples is as much as 38 bank. The analytical method used is multiple linear regression analysis.This result show that ATM has a significant positive effect on financial performance. While mobile banking has not significant effect on financial performance. With ROA as a measure of financial performance